Plakat "Ja für unsere Bahn 2000 // ... damit unsere Randregionen den Anschluss nicht verpassen"
Verkehr;Landverkehr;Schienenverkehr;Bahn 2000 politischer Rahmen;Wahlen und Abstimmungen;Volksabstimmung